Hubungan Antara Beban Kerja Dengan Kelelahan Kerja Pada Petugas Cleaning Service Di Rumah Sakit PKU Muhammadiyah Surakarta - Ratnasari, Novita; , dr.Hardjanto, MS., SpOK; , Sri Darnoto, SKM., MPH (2016)
The cleaning service in generally do the same cleaning maintenance every day. But each of the officers did not always get the same task due to the additional tasks. Erratic Additional tasks make workload of each official different. Workload with the increasing could reduce the effectiveness of our work , the reduction of the capacity of work and resiliency of the body , so there arose to be exhausted. When fatigue symptoms it goes on and performance will decline and work errors will increase until it ends with the occurrence of a work accident. The purpose of this research is to find the relationship between workload with work fatigue of the cleaning service in PKU Muhammadiyah Surakarta hospital. The methodology it uses analytic observational design by approach cross-sectional. The population research is the cleaning service as many as 61 people in PKU Muhammadiyah Surakarta Hospital. An election samples with purposive sampling about 37 people. The result with statistical tests use the rank spearman showed that is no link between workload with work fatigue (p=0,000) of the cleaning service in PKU Muhammadiyah Surakarta hospital.